Role of Chitin for Harbouring of Toxigenic Vibrio cholerae O1 El Tor in Aquatic Environment (Bangladesh Journal of Microbiology, 2010)
Vibrio cholerae, the etiological agent of cholera is an autochthonous bacterium of aquatic environment, often found attached to crustacean zooplankton. Chitin is the main component of crustacean exoskeleton, an insoluble polysaccharide. V. cholerae can secrete chitinase enzymes, which can facilitate the bacterium's association with chitinous aquatic organisms to utilize it as a potential nutrient source. In the present study, we checked the role of chitin for long term survival of V. cholerae. Laboratory based microcosms were prepared with purified artificial chitin chips and a toxigenic strain of V. cholerae O1 El Tor. In the presence of chitin, V. cholerae was found in a higher cellular density for >61 days in culturable condition than control water. We observed that the older chitin chips gradually thinner which indicated that V. cholerae utilized chitin. PCR experiment confirmed the presence of the bacterium's cholera toxin coding gene (ctxA) and membrane associated virulent gene ompU remained unaltered. Finally, from randomly amplified polymorphic DNA (RAPD) analysis no significant genotypic variation was detected in the bacterium's genome after its long time association with chitin. Keywords: Vibrio cholerae; Chitin; Polymerase chain reaction (PCR); MicrocosmDOI: http://dx.doi.org/10.3329/bjm.v25i1.4851 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 26-30